How can scanned proton beam treatment planning for low-grade glioma cope with increased distal RBE and locally increased radiosensitivity for late MR-detected brain lesions? - Bauer, Julia; Bahn, Emanuel; Harrabi, Semi B.; Herfarth, Klaus; Debus, Jürgen; Alber, Markus (Medical physics, 2021)
A novel risk model has recently been proposed for the occurrence of late contrast-enhancing brain lesions (CEBLs) after proton irradiation of low-grade glioma (LGG) patients. It predicts a strong dependence on dose-weighted linear-energy transfer (LETd effect) and an increased radiosensitivity of the ventricular proximity, a 4-mm fringe surrounding the ventricular system (VP4mm effect). On this basis, we investigated (A) how these two risk factors and patient-specific anatomical and treatment plan (TP) features contribute to normal tissue complication probability (NTCP) and (B) if conventional LETd-reduction techniques like multiple-field TP are able to reduce NTCP. (A) The LGG model cohort (N = 110) was stratified with respect to prescribed dose, tumor grade, and treatment field configuration. NTCP predictions and CEBL occurrence rates per strata were analyzed. (B) The effect of multiple-field TP was investigated in two patient groups: (i) nine high-risk subjects with extended lateral target volumes who had developed CEBLs after single-beam treatments were retrospectively replanned with a clinical standard two-field setting using almost orthogonal fields and strictly opposing fields, (ii) single-field treatments were simulated for seven low-risk patients with small central target volumes clinically treated with two strictly opposing fields. (A) In the model cohort, we identified the exposure of the radiosensitive VP4mm fringe with proton field components of increased biological effectiveness as dominant NTCP driving factor. We observed that larger target volumes and location lateral to the main ventricles, both being characteristic for WHO°II tumors, presented with the highest complication risks. Among subjects of an equal dose prescription of 54 Gy(RBE), the highest median NTCP was obtained for the WHO°II group treated with two fields using sharp angles. (B) Regarding the effect of multiple-field plans, we found that an NTCP reduction was only achievable in the low-risk group where the LETd effect dominates and the VP4mm effect is small. NTCP of the single-field plans was 23% higher compared to the clinical opposing field plan. In the high-risk group, where the VP4mm effect dominates the risk, both two-field scenarios yielded 44% higher NTCP predictions compared to the clinical single-field plans. The interplay of an increased radiosensitivity in the VP4mm fringe with proton field components of increased biological effectiveness creates a geometric complexity that can hardly be managed by current clinical TP. Our results underline that advanced biologically guided TP approaches become crucial for an effective risk minimization in proton therapy of LGG.
Gesehen am 15.09.2023